Surface site modulations by conjugated organic molecules to enhance visible light activity of ZnO nanostructures in photocatalytic water splitting - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Journal of Physical Chemistry C, 2015)
Surface modification of ZnO nanoparticles is identified as a method of modulating surface sites advantageously. ZnO nanoparticles of two different sizes are surface modified with a conjugated organic moiety to enable electron conduction and transfer. Enhanced H-2 evolution from water-methanol mixtures was observed in the composite systems compared to pristine ZnO under visible light irradiation without any cocatalyst. The system is also marginally active in water splitting in pure water without any sacrificial agents. Photophysical characterization indicates that even though reducing size into the nanoregime affects the band gap detrimentally, modifications by simple conjugated organic molecules assist in enhanced visible light activity. The experimental observations are corroborated with computational studies, which also point to a localization of valence band maximum of the interface on the organic moiety and conduction band minimum on ZnO.

Sensitizing with short conjugated molecules: multimodal anchoring on ZnO nanoparticles for enhanced electron transfer characteristics, stability and H-2 evolution - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Catalysis Today, 2018)
Sensitizing semiconductors with organic dyes is usually employed to improve efficiency of semiconductors towards visible light absorption and charge transport. However, till date most of the dyes are either noble metal based with complex and expensive synthesis procedure or have a very narrow absorption band. Further the photostability of the dyes is another important issue. In this work we have studied, using a combination of photophysical and computational methods, ZnO nanoparticles sensitized with transition metal free, cheap and easy to synthesize azoquinoline dye that has been designed to have multiple chelating sites, viz., carboxylic group and hydroxyl imine group as a photocatalyst for water splitting activity. We find that the presence of multiple chelating sites facilitates dual mode of anchoring on ZnO nanoparticles, which leads to enhanced photostability and H-2 generation of the composite. This is attributed to the incorporation of resonance features in the dye that increases electron transfer between ZnO and dye in contrast to the charge accumulation and photo degradation observed in non-conjugated and single site anchoring counterparts. Electron transfer from ZnO to dye under UV light and reverse in visible light could be identified experimentally. Such simple designing aspects can aid in identifying better catalysts for photocatalytic water splitting.